STRATEGI GURU DALAM MENINGKATKAN PERKEMBANGAN KEAGAMAAN SISWA DI RAUDHATUL ATHFAL NURUL HUDA DESA LANG-LANG KECAMATAN SINGOSARI KABUPATEN MALANG - Ika Putri Hardiana; Anwar Sa’dullah; Yorita Febry Lismanda (Jurnal Dewantara, 2020)
This study aims to describe the religious development of students in Raudhatul Athfal Nurul Huda Lang-Lang Village Singosari District Malang Regency and to identify supporting and inhibiting factors in religious development in Raudhatul Athfal Nurul Huda Lang-Lang Village Singosari District Malang Regency. This research was conducted at RA Nurul Huda which is located in a neighborhood close to the educational environment. This study uses qualitative research methods using data triangulation techniques. The results of this study are (1) has four strategies, namely: First Instill love to Allah SWT. Second is Touching and activating students' thinking potential. Third is giving awards to students. (2) The inhibiting factor is the unequal pattern of care at school and at home, and maybe after time has changed and will often share together between school and parents about how good parenting is in accordance with existing values and there must be constraints. The supporting factor for the success of religious development is that children are given positive knowledge and examples of actions taken by teachers at school.